2001
DOI: 10.1016/s1074-5521(01)00040-0
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the orthosomycin antibiotic avilamycin A: deductions from the molecular analysis of the avi biosynthetic gene cluster of Streptomyces viridochromogenes Tü57 and production of new antibiotics

Abstract: The avilamycin A biosynthetic gene cluster represents an interesting system to study the formation and attachment of unusual deoxysugars. Several enzymes putatively responsible for specific steps of this pathway could be assigned. Two genes encoding enzymes involved in post-PKS tailoring reactions were deleted allowing the production of new analogues of avilamycin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 54 publications
(61 reference statements)
2
118
0
4
Order By: Relevance
“…The amino acid sequence deduced from cpz23 shows highest overall homology to several hypothetical proteins from Streptomyces including AviX9 of the avilamycin gene cluster from Streptomyces viridochromogenes (50). According to the conserved protein domain search the C terminus of Cpz23 is similar to SGNH-hydrolases, a diverse family of lipases and carboxyesterases (51).…”
Section: Identification and Cloning Of The Caprazamycin Gene Cluster-mentioning
confidence: 99%
“…The amino acid sequence deduced from cpz23 shows highest overall homology to several hypothetical proteins from Streptomyces including AviX9 of the avilamycin gene cluster from Streptomyces viridochromogenes (50). According to the conserved protein domain search the C terminus of Cpz23 is similar to SGNH-hydrolases, a diverse family of lipases and carboxyesterases (51).…”
Section: Identification and Cloning Of The Caprazamycin Gene Cluster-mentioning
confidence: 99%
“…calO4, aviN and evrI, are also found in the biosynthetic clusters of calicheamicin (Ahlert et al, 2002), avilamycin A (Weitnauer et al, 2001) and evernimicin (Hosted et al, 2001), respectively. It has been proposed that they may control the starter unit for orsellenic acid biosynthesis, based on their sequence similarity to dpsC (Hosted et al, 2001;Weitnauer et al, 2001). However, their function has not been proven experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…calO4 of the calicheamicin biosynthetic gene cluster in Micromonospora echinospora subsp. calichensis (47 % identity at the amino acid level) (Ahlert et al, 2002), aviN of the avilamycin A cluster in Streptomyces viridochromogenes (45 % identity) (Weitnauer et al, 2001) and evrI of the evernimicin cluster in Micromonospora carbonacea var. africana ATCC 39149 (44 % identity) (Hosted et al, 2001).…”
Section: Sequence Analysis Of Clon2mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that within the avilamycin biosynthetic cluster in Streptomyces viridochromogenes, a set of putative α-ketoglutarate, nonheme iron-dependent [AKG/Fe(II)-dependent] oxygenases may be capable of catalyzing both orthoester linkage and methylenedioxy bridge formation (9,10). AKG/Fe(II)-dependent oxygenases are powerful oxidants that catalyze a range of reactions, including oxidative cyclizations, hydroxylations, peroxidations, epoxidations, desaturations, and halogenations (11)(12)(13)(14).…”
mentioning
confidence: 99%